Endoscopic Ultrasound-Guided Fine Needle Aspiration and Biopsy in Gastrointestinal Subepithelial Tumors - Gyu Young Pih; Do Hoon Kim (Korean Society of Gastrointestinal Endoscopy, 2019)
The incidence of asymptomatic and incidentally found upper gastrointestinal subepithelial tumors (SETs) is increasing with the implementation of national cancer screening and the development of high-resolution endoscopy in Korea. However, endoscopy alone cannot be used to determine whether SETs are benign or malignant. Endoscopic ultrasound (EUS) is used to further characterize these lesions through the examination of their layered structure, internal echogenicity, size, and relationship to the extramural structure. These provide additional information on whether the lesion is benign or malignant. Nevertheless, the sensitivity and specificity of EUS alone in predicting malignancy is unsatisfactory. Recent guidelines have recommended deciding the timing of EUS-fine needle aspiration and biopsy (EUS-FNA/B) for SETs based on tumor size, malignant features on endoscopy, and high-risk features on EUS. The diagnostic accuracy of EUS-FNA/B is reportedly influenced by factors including needle size, number of needle passes, use of suction, use of a stylet in the needle assembly, fanning technique, availability of an on-site cytopathologist, and experience of the endosonographer. Therefore, according to the characteristics of the SETs, various subsequent methods and techniques should be appropriately employed to improve the diagnostic yield of EUS-FNA/B.